Enhancing Cloud-Native Applications: A Comparative Study of Java-To-Go Micro Services Migration - Sairamakrishna BuchiReddy Karri; Chandra Mouli Penugonda; Srujana Karanam; Mohd Tajammul; Srinivasarao Rayankula; Prasad Vankadara (International Transactions on Electrical Engineering and Computer Science)
Moving microservices from Java to Go creates great opportunities for performance, scalability, and resource efficiency. Nonetheless, such a move comes with other challenges related to infrastructure changes, deployment strategies, observability, and security. This paper tries to look at elements of paramount importance as concerned with Java-to-Go migration, thereby, interrogating the key hosting environments, containerization, and orchestration. Go as a light engine introduces one of the most cost-effective deployments as organizations lean towards cloud-native architectures and Kubernetes-based orchestration [24]. The transition likewise demands adaptation of the observability practices since Go applications utilize different tools compared to Java applications. Security topics currently include dependency management, API protection, and vulnerability scanning which are highly pertinent in keeping the application intact. However, with proper planning, these challenges can leverage the advantages Go provides, ultimately presenting it as an attractive option for microservices development. Future studies should look into automated migration tools, the process of standardized best practices, and refinements to security to ease this transition.